SOCIAL COMMUNICATIONS – WEAPONS OF MASS DESTRUCTION. REFLECTIONS VICTIM - Petrova, Hanna А. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
On the example of the Donetsk Regional Universal Scientific Library shows the place of library as a social institute, changes in the organization of library work in period of coexistence of diverse political and social forces and its influence on the ideological, social and political processes in society.